Do textbooks support incidental vocabulary learning? – a corpus-based study of Swedish intermediate EFL materials - Denise Bergström; Cathrine Norberg; Marie Nordlund (Education Inquiry)
Learning vocabulary is a central but yet complex aspect of learning a language. Hence, researchers stress the importance of facilitating vocabulary development via a structured approach to target words and recycling. While teaching materials have the potential to provide this structure to all students in a classroom, few studies have investigated the vocabulary component of textbooks and the learning opportunities they provide. In the present study, the texts in five series of EFL materials aimed at intermediate learners in Swedish secondary school (years 7–9) were investigated, using corpus-based methods. The results indicate that the texts encompass a suitable amount of unknown vocabulary for vocabulary learning from reading and provide exposure to mid-frequency vocabulary. However, it was also found that these items are not recycled sufficiently. Rather, the materials mainly recycle lexical items that students are likely to know already. It is therefore concluded that although the materials offer input suitable for the target students, they are not structured in a way that supports vocabulary development.